ANALISIS SISTEM INFORMASI AKUNTANSI PADA SIKLUS PENDAPATAN DARI PENERIMAAN KAS PADA LPD DESA ADAT KAPAL - Kadek Devi Kalfika Anggria Wardani; I Putu Gede Ferry Andhika (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The more complicated the cash receipts activity carried out by a company, the more it will affect the recording of the company's cash receipts which will be longer and more complicated, especially if it is still done manually, therefore, along with technological developments, companies are required to implement information systems in every business. The company's activities are no exception to activities in the income cycle. The income cycle at the Kapal Adat Village LPD is quite complicated and mostly focuses on the credit distribution process, but most of these activities are still carried out manually. both in the application of accounting information systems in their respective fields. Therefore, this activity aims to find out how the accounting information system is applied to the income cycle in cash receipts at the Kapal Adat Village LPD. This activity uses the method of observation, interviews and documentation. From the results of this activity, it is known that the income cycle on cash receipts in the LPD of the Traditional Kapal village is still quite complicated because it has not fully implemented the accounting information system in cash receipts activities.